Multi level moving storage rack / Muhamad Hafizudin Muhammad ... [et al.] - Muhammad Rosli, Muhamad Hafizudin; Ariffin, Anas; Roslan, Aiman Asyraaf; Nor Aznan, Muhammad Aqil Akhtar; Jamaludin, Lukman Hakim (2021)
The purpose of this project is to design an industrial storage system that mostly takes up vertical space without the need of ladders and forklifts. Various engineering concepts and methods are put into this project in order for it to have the optimum strength, durability, performance and safety so that it can achieve its purpose. This project consists of several individual parts which are the internal mechanism, the platforms, the fram, the belt system, the motor and the external body. Each of the parts has its own important role in order for the product to achieve it’s main objective with high efficiency and safety